Implementasi Pendidikan Karakter untuk Meningkatkan Nilai Moral Siswa di SDIT Ash-Shofa - Maulida Saqinah (Jurnal Indonesia Sosial Sains, 2022)
The inculcation of social values ​​in schools is an effective aspect. However, what happens is that learning in schools always prioritizes cognitive aspects over effective aspects. Sometimes there are still schools that think that the success of attitudes and behavior is much more important. This study aims to determine the importance of character education for students who lack the attitude and behavior of respecting teachers and other people around them, as well as developing moral values ​​for children at SDIT Ash-Shofa North Bekasi. This research was conducted in 2021/2022. The research method used is descriptive qualitative. Data collection techniques used in the form of interviews, observation, and documentation. Interview data retrieval consisted of class II homeroom teachers and 5 students at SDIT Ash-Shofa, North Bekasi. The conclusion in this study is the application of character education obtained from moral cultivation to students who have more good morals and students can also imitate good habits. Informants carry out the application or implementation of character education to students to improve students' morale so that they can understand polite, good, and honest behavior. This is done by habituation. The habituation is applied before and after carrying out the Teaching and Learning Activities (KBM).